Is there a rating bias of job candidates based on gender and parenthood? A laboratory experiment on hiring for an accounting job - Erlandsson Anni; Bygren Magnus; Gähler Michael (SAGE PUBLICATIONS LTD, 2025)
Biased practices by employers have been suggested as one possible cause for the observed gender disparities in labor market outcomes. While US-based laboratory experiments show a clear motherhood penalty in recruitment, European laboratory experiments on the topic are to our knowledge lacking. We conducted a laboratory experiment with 228 university students to study a potential gender bias in the evaluation of (fictitious) job candidates for an accounting manager position, and how recruitment decisions are made. We explore two dimensions of decision-making, that is, evaluators' individual ratings and collectively made ratings. The results show a statistically significant gender bias in job applicant ratings in favor of female applicants. Thus, female job applicants are more often than male applicants rated as the top candidates, regardless of their parental status. Also, we find no motherhood penalty in the applicant ratings. Moreover, there is a statistically significant pro-female bias in applicant ratings made by female evaluators individually and by all-female evaluation groups.